Increasing Knowledge and Skills of Mothers with Stunted and Malnourished Toddlers in Processing Local Foods for Nutritional Problem Solving - Resmiati Resmiati; Yeffi Masnarivan; Rahmi Awalina (Universitas Lambung Mangkurat, 2024)
Stunting and malnutrition are significant nutritional problems faced today. Nutritional education for mothers of toddlers is critical in addressing this challenge. This activity aims to enhance the understanding of mothers of toddlers regarding nutrition and child development and improve their skills in processing local foods for toddler meals. This activity was carried out at Posyandu Harapan Ibu 6 in Mata Air Village, South Padang District, from September 23 to October 19, 2023, involving 15 mothers of stunted and malnourished toddlers. The method used was Participatory Action Research (PAR), which included several activities such as participatory education on nutrition, child development, and parenting, the nutritional value of local foods, and family healthy menus based on local foods, as well as direct assistance in the form of local foods to be processed into healthy toddler meals. The result of this activity was an increase in the understanding of mothers of toddlers about nutrition and child development from 30% to 80%, as assessed through participatory discussions and Q&A sessions at the end of the education session. Additionally, there was an improvement in the mothers' skills in processing local foods, with an average score of 6 out of 7, evaluated from the food processing outcomes documented through photos over ten consecutive days. This activity concludes that nutrition education based on PAR effectively increases the knowledge and skills of mothers of toddlers, making it a replicable intervention model in other areas to address nutritional problems and stunting.